PENATALAKSANAAN FRAKTUR ELLIS KELAS III 11 DENGAN PULPEKTOMI DAN RESTORASI MAHKOTA PASAK - Sidiartha, I Gusti Ayu Fienna Novianthi; Parama, Putu Wiswananta (Interdental: Jurnal Kedokteran Gigi, 2020)
A 19-year-old male patient came to Unud Hospital with a complaint that his upper right front tooth was broken. The patient's right front toothaches when he consumes cold food or drinks and bleeds every morning. Pain still exists even if food or cold drinks are removed. Complaints felt since 7 months ago. The tooth now feels pain but is not as severe as the initial tooth fracture. Patients have consumed mefenamic acid to reduce pain. The tooth has never been treated by a dentist. The patient is now treated with pulpectomy accompanied by a fused to metal porcelain jacket crown restoration with a cast post-core. After controlling for one week after treatment, the desired result is the loss of subjective and objective complaints in the patient.